Miniature at Large - Tomáš Dvořák (Interfaces)
By discussing Claude Lévi-Strauss’s concept and use of the reduced model and the historical development of portrait miniatures and art reproductions, this article demonstrates that the process of image miniaturization is integral to, and congruent with, the process of establishing larger image infrastructures and the rescaling of visual culture towards the numerous, instrumental, and generic. The article sets out with an analysis of reproductions in Lévi-Strauss’s La Pensée sauvage to show how they participate in recursive chains of miniaturization or reduction of complexity. The reduction of dimensions, qualities, or the substitution of a detail for a whole simultaneously produces a generic model that is prone to multiplication and mobility. This process is exemplified by the development of portrait miniatures and their transition to photography via mechanical instruments of reproduction. The article concludes by highlighting the miniature character of photography in physical, discursive, and technical sense.